Case study for Pelorus Intelligence and Technology Academy Sdn. Bhd. : SWOT analysis for Netherlands Maritime Institute of Technology (NMIT) / Nur Syafiqah Nor Rashid - Nor Rashid, Nur Syafiqah (Faculty of Business and Management, 2010)
SWOT analysis is a tool for auditing in an organization and its environment. SWOT analysis is the first stage of planning and helps marketers to focus on key issues before any decision can be made. This case study analyses the strength, weakness, opportunity and threat or known as SWOT Analyses on Netherlands Maritime Institute of Technology (NMIT) for PELORUS Intelligence and Technology Academy Sdn. Bhd. This case study first will identify as many as possible factor for each element’s, then the researcher will select the major factor for each element’s and conduct research to support each factor.